Pengaruh Waktu Reaksi dan Laju Alir Oksigen Pada Proses Delignifikasi Tandan Kosong Kelapa Sawit - Miftahul Jannah, Asyeni; Fitria, Syarifah; Muharomah, Riani; Putri Andini, Handalia; Bonawati, Annisa (Jurnal Ilmiah Teknik Kimia, 2025)
Oil palm empty fruit bunches have a high lignocellulose content. Lignocellulose consists of hemicellulose, cellulose, and lignin. Lignin is the binder of cells in biomass. The structure of lignin is very complex and difficult to break down. The presence of lignin will hinder the processing of OPEFB and need to do delignification. One effective way to reduce lignin content is by ozonolysis. In this study, the effect of reaction time and oxygen flow rate on the OPEFB was studied. The reaction times in this process were 5, 10, and 15 min, and oxygen flowrates were 1, 2, 3 L/min. Lignin content was analyzed using the Kappa method. The least lignin content was obtained in the sample with 2 L/min flow rate for 5 min, which was 11.01% with a cellulose content was 64.72% and hemicellulose was 15.16%.